The Teaching of Intermediate Grammar Using A Student Centered Learning Approach - Rombepajung, Paula; Anabokay, Yanrini Martha; Sailun, Betty (English Education Department, 2023)
The active learning component of the student centered learning strategy involves students working in teams to complete projects and solve issues They also ask and answer their own questions discuss topics and provide explanations in class This study intends to examine how lecturers view the student centered learning strategy when teaching intermediate grammar to second graders in higher education It also seeks to ascertain how effective this technique is in this setting This study specifically responds to the following queries: 1 How do the teachers feel about implementing a student centered learning strategy when instructing intermediate English grammar? 2 How do the pre test and post test results of the control and experimental groups compare? An experimental research design was used in this study The control group and the experimental group are the two groups that make up this study First graders in the experimental group were steered through student centered education to improve their command of intermediate grammar The findings demonstrated that student centered learning was highly successful while instructor perceptions were favorable neutral and negative So there are still pros and cons if teaching grammar uses a student centered learning approach< p>